Afectaciones Psicológicas Desarrolladas por Tres Cuidadores Familiares debido a la atención de pacientes Oncológicos en los municipios de Bolívar y Zarzal, Valle del Cauca (2021)
The role of the caregiver of an oncology patient is performed in most cases by their family members. In which, stressful and overload situations can be originated, which often directly affects their physical and psychological health, producing alterations such as: depression, anxiety, stress, irritability and other affectations, which can vary from one individual to another, it is taken into account that each person has different coping strategies when dealing with stressful situations. Objective: To determine the most frequent psychological affectations that three family caregivers developed due to the care of cancer patients in the municipalities of Bolívar and Zarzal, Valle del Cauca. Method: The research has a qualitative and descriptive approach, carried out during four months, in the municipalities of Bolívar and Zarzal Valle del Cauca. Three instruments were applied: semi-structured interview, focal life history and Zarit caregiver burden scale, in order to characterize the different affectations present in family caregivers of cancer patients. Results: The symptoms of the psychological affectations, developed by the family caregivers of cancer patients participating in the research, were: Anxiety, Stress, Irritability, Depression and alterations in Family Dynamics, determined by the application of the different instruments to said participants. Conclusion: Providing care to an oncological patient requires a lot of support, mainly from the family group. Because, caring for him at home represents a substantial change for the family, especially due to the prolonged time of treatment, which frequently produces a series of symptoms that are physically and emotionally exhausting. Where, the work of the family caregiver becomes relevant, not only for direct patient care, but also for its role in the maintenance, cohesion and possible overcoming of the patient's illness.